Pengaruh Keteladanan Guru Pendidikan Agama Kristen Terhadap Karakter Siswa Di Kelas VIII SMP Negeri 4 Pollung Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Aknes Diana Silaban; Wilson Simanjuntak; Taripar Aripin Samosir; Damayanti Nababan; Ronny Simatupang (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The research aims to determine the positive and significant influence of exemplary Christian Religious Education teachers on the character of students in class VIII of SMP Negeri 4 Pollung for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the example of Christian Religious Education teachers on the character of class VIII students at SMP Negeri 4 Pollung for the 2023/2024 academic year. Descriptive quantitative research method. The population of all class VIII students at SMP Negeri 4 Pollung for the 2023/2024 academic year who are Protestant Christians is 102 people. Sampling was taken using Random Sampling technique (randomly) of 40% of the total population, namely 40 people. The research instrument is a closed questionnaire. The results of data analysis obtained: 1) regression equation. 2) The determination test revealed that the influence was 37.09%. 3) Testing the hypothesis obtained tcount=4.748>ttable=2.021, so H0 is rejected and Ha is accepted, namely that there is a positive and significant influence between the example of Christian Religious Education teachers on the character of class VIII students at SMP Negeri 4 Pollung for the 2023/2024 academic year.